APA Handbook of Research Methods in Psychology: Foundations, Planning, Measures, and Psychometrics (Vol. 1) (2nd Ed.). 2023
DOI: 10.1037/0000318-037
|View full text |Cite
|
Sign up to set email alerts
|

Item response theory.

Abstract: refers to a class of mathematical models relating individual differences on one or more latent variables to the probability of responding to a scale item in a specific response category. A response of 3 on a 5-point personality item, a correct answer on a multiple-choice item, and a clinician' s rating of an adolescent' s anxiety are all item responses that can potentially be related (probabilistically) to a latent variable. IRT models, which focus on characterizing how individual differences on a latent varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…3. It's crucial to examine the relationship between student abilities and item di culty levels within the framework of latent variables, a possibility afforded by the mathematical model system in IRT [10]. This IRT technique also aims to enhance accuracy in performance classi cation [11], [12].…”
Section: Resultsmentioning
confidence: 99%
“…3. It's crucial to examine the relationship between student abilities and item di culty levels within the framework of latent variables, a possibility afforded by the mathematical model system in IRT [10]. This IRT technique also aims to enhance accuracy in performance classi cation [11], [12].…”
Section: Resultsmentioning
confidence: 99%
“…Gessaroli and De Champlain's (1996) research found that identification of a second factor may increase with test length in dominance data fitting a 2-parameter logistic model. Drasgow and Hulin (1990) also noted that their unidimensional data appeared to be multidimensional with sample sizes of 750 (using modified parallel analysis) however this effect disappeared when the sample size increased to 5000. Therefore, the multidimensional finding for the 40-item clean datasets is likely due to sampling error and may be reduced with an increase in sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The basic idea in IRT models is that educational and psychological attributes (e.g., anxiety/stress, knowledge, attitude, etc.) are abstract latent entities that can be measured if they are elicited through devices called tests [2,3]. In fact, the responses of individuals to items of a test are observable manifestations of the hypothesized latent trait.…”
Section: Introductionmentioning
confidence: 99%